2009
DOI: 10.4076/1752-1947-3-8389
|View full text |Cite
|
Sign up to set email alerts
|

Distal migration of a floating carotid thrombus in a patient using oral contraceptives: a case report

Abstract: IntroductionWe report the case of a patient with distal migration of a floating carotid thrombus caused by oral contraceptives.Case presentationA 48-year-old woman using oral contraceptives suffered from dysarthria and gait disturbance. Examinations, including ultrasound and cerebral arteriogram, revealed a floating thrombus at the left carotid bifurcation with no stenosis. Despite antithrombotic therapy, the floating carotid thrombus migrated to the ipsilateral middle cerebral artery, resulting in a severe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…So far, TM has been described in a small cohort study in which reactive hyperemia in the MCA territory has been interpreted as a sign of TM or in studies in which sequential transcranial Doppler was performed in patients suffering from intracranial large vessel occlusions . Further, TM has been witnessed and reported anecdotally in the form of case reports during diagnostic or therapeutic angiography or sequential CTAs . However, neither its incidence nor its dependency on the administration of intravenous (IV) recombinant tissue plasminogen activator (rtPA) or its relevance for ET has been studied systematically.…”
Section: Introductionmentioning
confidence: 99%
“…So far, TM has been described in a small cohort study in which reactive hyperemia in the MCA territory has been interpreted as a sign of TM or in studies in which sequential transcranial Doppler was performed in patients suffering from intracranial large vessel occlusions . Further, TM has been witnessed and reported anecdotally in the form of case reports during diagnostic or therapeutic angiography or sequential CTAs . However, neither its incidence nor its dependency on the administration of intravenous (IV) recombinant tissue plasminogen activator (rtPA) or its relevance for ET has been studied systematically.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of these is diverse, with atheromatous plaque complications (ulceration, intraplaque hemorrhage) being the most common cause. Other causes and associations include hypercoagulable states, autoimmune disorders, carotid aneurysms, cardiogenic emboli and arterial dissections 4. Our patient had a non-stenotic atheromatous plaque at the level of the FFT.…”
Section: Discussionmentioning
confidence: 70%
“…FFT of the carotid artery is extremely rare, with around 150 cases reported in the literature1 3 and an incidence of 0.4–1.5% in previous angiographic studies of cases of ischemic cerebrovascular disease;2 4 however, this may be an underestimation of the disease. Ruptured plaques at the carotid bifurcation are more common causes of acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imai et al 13 reported a patient with acute stroke who deteriorated despite maximal anticoagulation and antiplatelet therapy for a high-grade carotid stenosis with ILT. Watanabe et al 14 reported a patient with acute stroke in whom ILT migrated to the ipsilateral middle cerebral artery resulting in a serious stroke 4 days after starting antithrombotic therapy. Maximal anticoagulation and antiplatelet therapy is usually started to eliminate the ILT but cannot always prevent neurological deterioration, although Comb et al 2 reported that antithrombotic therapy was effective in eliminating ILT in five of six patients.…”
Section: Discussionmentioning
confidence: 99%